Trend analysis of multi-level determinants of maternal and newborn postnatal care utilization in Pakistan from 2006 to 2018: Evidence from Pakistan Demographic and Health Surveys - Sarosh Iqbal; Sidra Maqsood; Rubeena Zakar; Florian Fischer (BMC, 2023)
Abstract Background Postnatal care (PNC) is crucial for maternal and newborn health. Healthcare-seeking practices within the postpartum period help healthcare providers in early detection of complications related to childbirth and post-delivery period. This study aims to investigate trends of PNC utilization from 2006 to 2018, and to explore the effects of multi-level determinants of both maternal and newborn PNC in Pakistan. Methods Secondary data analysis of the last three waves of the nationally representative Pakistan Demographic and Health Surveys (PDHSs) was conducted Analysis was limited to all those women who had delivered a child during the last 5 years preceding each wave of PDHS Bivariate and multivariate logistic regression was applied to determine the association of maternal and newborn PNC utilization with multi-level determinants at individual, community, and institutional levels. Results In Pakistan, an upward linear trend in maternal PNC utilization was found, with an increase from 43.5 to 63.6% from 2006 to 2018. However, a non-linear trend was observed in newborn PNC utilization, with an upsurge from 20.6 to 50.5% from 2006 to 2013, nonetheless a decrease of 30.7% in 2018. Furthermore, the results highlighted that the likelihood of maternal and newborn PNC utilization was higher amongst older age women, who completed some years of schooling, were employed, had decision-making and emotional autonomy, had caesarean sections, and delivered at health facilities by skilled birth attendants. Multivariate analysis also revealed higher odds for women of older age, who had decision-making and emotional autonomy, and had caesarean section deliveries over the period of 2006-2018 for both maternal and newborn PNC utilization. Further, higher odds for maternal PNC utilization were found with parity and size of newborn, while less for ANC attendance and available means of transportation. Furthermore, increased odds were recorded for newborn PNC utilization with the number of children, ANC attendance, gender of child and mass media exposure from 2006 to 18. Conclusion A difference in maternal and newborn PNC utilization was found in Pakistan, attributed to multiple individual (socio-demographic and obstetrics), community, and institutional level determinants. Overall, findings suggest the need to promote the benefits of PNC for early diagnosis of postpartum complications and to plan effective public health interventions to enhance women's access to healthcare facilities and skilled birth assistance to save mothers' and newborns' lives.